Indigenising Australian Studies in China. Issue 2 (3rd April 2021) - McCarthy, Gregory
ABSTRACT: Since the formalisation of Australian studies in China in the early 1980s, over 30 Australian studies centres are now spread across China, with a lively network of scholars, exemplified by undergraduate and postgraduate enrolments of principally Australian literature, a Chinese-based Australian studies journal, and a large biennial conference. The success of Australian studies in China is the result of many interweaving threads: commitment of Chinese higher institutions, prominent individual sponsors, people-to-people ties, university-to-university relationships, and diplomatic creativities. This article argues that the success of Australian studies in China is underpinned by its indigenisation: the process by which Australian literature is reframed and textually reinterpreted as an indigenised form of humanism to suit the Chinese literary sensibilities and the political environment in which they operate. In particular, the article highlights how this indigenisation or Sinicisation of Australian studies creates cross-cultural complexities and tensions that have prompted the Australian side to adapt to a unique form of Australian studies that conforms to Australian norms and the aims of diplomatic soft power.